THE EFFECTIVENESS OF ONLINE GAME IN TEACHING VOCABULARY OF THE FIRST GRADE OF MTs NEGERI 1 KEDIRI - Lyana, Uswatul (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2019)
The aim of the research was to analyze whether there is any effectiveness of online game in teaching vocabulary of the first grade of MTsN 1 Kediri. This research was quantitative research approach, the research design was quasy experimental by non equivalent group posttest-only. This research used two classes which became experimental group (VII C) and control group (VII E). The experimental group was taught by using online game, whereas control group was taught without online game. The instruments used in the research was multiple choice test. The procedures of using online game in teaching vocabulary are; preparation, main activities and post activity. The reasearch took 4 meetings and 1 meeting to do test. The result is online game in teaching vocabulary is effective. It can be proven by the result of t-test: the mean score of experimental group (M = 88.29) was higher than control group (M = 83.92), and independent-samples t-test which values of the sig. 2-tailed was 0.29% or 0.029 and 0.029 < 0,05. This result suggests that the use of media online game in teaching vocabulary is interesting way to learn English.